2018
DOI: 10.1093/toxsci/kfy267
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Neurotoxicants Induce ALS-Linked TDP-43 Pathology

Abstract: Heavy metals, such as lead, mercury, and selenium, have been epidemiologically linked with a risk of ALS, but a molecular mechanism proving the connection has not been shown. A screen of putative developmental neurotoxins demonstrated that heavy metals (lead, mercury, and tin) trigger accumulation of TDP-43 into nuclear granules with concomitant loss of diffuse nuclear TDP-43. Lead (Pb) and methyl mercury (MeHg) disrupt the homeostasis of TDP-43 in neurons, resulting in increased levels of transcript and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…In another study, a TDP-43 fragment with the RRM 1–2 domain via its histidine, cysteine, and glutamate residues that usually show affinity for zinc ions, was shown to aggregate in the presence of the zinc ions into ThT-staining rope-like aggregates (with hydrodynamic diameters: 300–1,000 nm) and also into small oligomeric structures (20–30 nm) (Garnier et al, 2017). Recently, Ash et al demonstrated that heavy metals, such as lead, mercury and tin, can trigger aggregation and formation of nuclear inclusions of TDP-43 in the PC12 cell lines (Ash et al, 2018). The exposure to lead and methyl mercury was found to disrupt the TDP-43's homeostasis in the neuronal cells and dysregulate its splicing activity.…”
Section: Emerging Mechanisms Of Tdp-43-induced Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a TDP-43 fragment with the RRM 1–2 domain via its histidine, cysteine, and glutamate residues that usually show affinity for zinc ions, was shown to aggregate in the presence of the zinc ions into ThT-staining rope-like aggregates (with hydrodynamic diameters: 300–1,000 nm) and also into small oligomeric structures (20–30 nm) (Garnier et al, 2017). Recently, Ash et al demonstrated that heavy metals, such as lead, mercury and tin, can trigger aggregation and formation of nuclear inclusions of TDP-43 in the PC12 cell lines (Ash et al, 2018). The exposure to lead and methyl mercury was found to disrupt the TDP-43's homeostasis in the neuronal cells and dysregulate its splicing activity.…”
Section: Emerging Mechanisms Of Tdp-43-induced Cytotoxicitymentioning
confidence: 99%
“…The exposure to lead and methyl mercury was found to disrupt the TDP-43's homeostasis in the neuronal cells and dysregulate its splicing activity. Also, lead could decrease the TDP-43 solubility and promote the phase separation of TDP-43 in vitro in a dose-dependent manner (Ash et al, 2018). Thus, the relationship between metal ion content and the TDP-43 functions and aggregation need thorough investigation.…”
Section: Emerging Mechanisms Of Tdp-43-induced Cytotoxicitymentioning
confidence: 99%
“…The protein sequences responsible for this property are a nuclear localisation sequence (NLS) in the N-terminus of the protein and on a putative nuclear export sequence (NES) (Borroni et al, 2019). In this respect, it is actually interesting to note that a selective inhibitor of nuclear export (KPT-335/350) could not enhance nuclear TDP-43 levels, despite having a mild neuroprotective effect in rodent cortical neurons from ALS/FTD models (Archbold et al, 2018). Nonetheless, in ALS disease, impaired nucleo-cytoplasmic transport of TDP-43 and other proteins seems one of the major alterations that are commonly observed in patients (Borroni et al, 2019).…”
Section: Nucleo-cytoplasmic Distribution Of Tdp-43mentioning
confidence: 99%
“…No aberrant changes in TDP‐43 distribution or phosphorylation were observed after prolonged exposure of mice to this compound (Pamphlett & Kum Jew, 2011). However, it has been recently reported that in primary hippocampal neurons from CD1 mice, the treatment with lead and methyl mercury (MeHg) was able to disrupt the homeostasis of TDP‐43 in neurons resulting in increased levels of transcript (Ash et al, 2019). Hexachlorophene.…”
Section: Expression Levels Of Tdp‐43 Within Cellsmentioning
confidence: 99%
“…Furthermore, serotonergic denervation leads to a loss of control on the inhibition of glutamate release, thus increasing its levels in the synaptic cleft, and identifying the importance of the serotonergic system at a neuroprotective level [ 20 ]. On the other hand, there has been evidence that there is a link between neurotoxicity due to high levels of heavy metals and the disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%